MENYELISIK PENGGUNAAN SEPEDA MOTOR DI KALANGAN PELAJAR (STUDI PADA PELAJAR SMP DI DENPASAR) - Karno, Ody Putra; Kebayantini, Ni Luh Nyoman; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
ABSTRACT Having a SIM (Permit Card to Drive) in the use of motorbikes as the main condition is not found by junior high school riders and the average age is still unpermitted. This research investigates and explains the phenomenon of motorcycle use among junior high school students in Denpasar City. The theory used in this study is the Social Action Hebert Mead which has four stages. The first stage is Impulse, where students get stimulation through. The second stage is Perception, in this stage the student will gather the stimuli this student has received and choose to respond to these stimuli. Then the third stage is Manipulation, where students will process the selection of stimuli. The last stage is Consumption, where students have chosen to use motorbikes as their actions. Therefore, stimulation in the family and external environment is crucial in the process of taking student action. Keywords: Motorcycle, Middle School Student, Social Action, Underage